Pengaruh Model Pembelajaran Science, Environment, Technology, And Society (SETS) Berbantuan HOTS Question Card Terhadap Kemampuan Berpikir Kritis Siswa SMP Pada Tema Ayo Siaga Bencana: Pengaruh Model Pembelajaran Science, Environment, Technology, And Society (SETS) Berbantuan HOTS Question Card Terhadap Kemampuan Berpikir Kritis Siswa SMP Pada Tema Ayo Siaga Bencana - Talia, Nita; Vitasari, Mudmainah; El Islami, R. Ahmad Zaky (PendIPA Journal of Science Education, 2025)
This study aims to determine the effect of the Science, Environment, Technology, and Society (SETS) learning model using HOTS Question Cards on junior high school students' critical thinking skills on the theme "Let's Be Prepared for Disasters." A quasi-experiment was used, using a non-equivalent control group design. Class VII A and class VII B, with 36 students in each class, constituted the population and sample. The sample was drawn using a purposive sampling technique. The instrument used was a critical thinking essay question sheet and an observation sheet. A t-test was used for data analysis. The results of the data analysis obtained a significant result (2-tailed) of 0.000 (0.000 <0.05). The conclusion was that H0 was rejected and Ha was accepted. This indicates that the Science, Environment, Technology, and Society (SETS) learning model using HOTS Question Cards influences junior high school students' critical thinking skills on the theme "Let's Be Prepared for Disasters."